THE CONTRIBUTION OF COLLABORATIVE LEARNING TO SPEAKING ABILITY AND SPEAKING ANXIETY AMONG IRAQI EFL LEARNERS - Al-Shammari, Hussein Ghanim (Antis-Publisher, 2026)
Objective: This study investigated the contribution of collaborative learning to speaking ability and speaking anxiety among Iraqi undergraduate EFL learners. Method: Employing a quasi-experimental design, the study involved 86 second-stage students from the English Department, Faculty of Education, University of Kufa, divided equally into experimental and control groups (n=43 each). The experimental group received collaborative learning instruction over a treatment period, while the control group was taught using conventional methods. Data were collected using a speaking test and the Foreign Language Classroom Anxiety Scale (FLCAS) administered as pre-tests and post-tests. Normality testing confirmed that parametric assumptions were met, and data were analyzed using paired samples t-tests and independent samples t-tests. Results: The findings revealed that the experimental group significantly outperformed the control group in speaking ability, with a mean post-test score of 64.57 compared to 48.23 (t(84) = -9.48, p < 0.001, d = 2.05). Furthermore, the experimental group demonstrated a substantial reduction in speaking anxiety, with a post-test mean of 48.34 compared to 64.23 in the control group (t(84) = 9.04, p < 0.001, d = 1.97). Novelty: These results indicate that collaborative learning not only enhances speaking proficiency but also significantly reduces speaking anxiety among Iraqi EFL learners. The study recommends the integration of collaborative learning strategies into EFL instruction to foster both linguistic competence and affective well-being.